2012
DOI: 10.1177/0363546512458218
|View full text |Cite
|
Sign up to set email alerts
|

Microfracture for Osteochondral Lesions of the Talus

Abstract: There were gross inconsistencies and an underreporting of data between studies such that pooling was deemed impossible. A concerted effort must be made by investigators to ensure that there is adequate reporting of data in studies of microfracture treatment for OLT. A set of guidelines to assist surgeons in reporting data may be useful for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Of those clinical studies “Procedure for assessing outcomes” and “Description of subject selection process” in Part B (primarily evaluates outcome criteria and recruitment rates) were significantly low. These findings are consistent with the outcomes found by a recent systematic review that analyzed the outcome data following microfracture for OLT in 24 clinical studies[ 36 ]. The authors found that approximately half of included studies did not have a patient history or patient-reported outcome data, despite the presence of well described general demographics and study design.…”
Section: Discussionsupporting
confidence: 90%
“…Of those clinical studies “Procedure for assessing outcomes” and “Description of subject selection process” in Part B (primarily evaluates outcome criteria and recruitment rates) were significantly low. These findings are consistent with the outcomes found by a recent systematic review that analyzed the outcome data following microfracture for OLT in 24 clinical studies[ 36 ]. The authors found that approximately half of included studies did not have a patient history or patient-reported outcome data, despite the presence of well described general demographics and study design.…”
Section: Discussionsupporting
confidence: 90%
“…Conservative therapy typically is used for Hepple modified magnetic resonance imaging (MRI) type I and milder type II injuries, which involve a smaller lesion area, stable exfoliated bone mass, and non-displaced talus cartilage [ 14 ], whereas surgery is require for Hepple type III to V injuries with severe symptoms, when conservative treatment for 3 to 6 months for talus cartilage injury with acute separation and displacement is ineffective, or the area of injury is large [ 15 , 16 ]. Reports in the literature underscore the fact that the area of the talus cartilage defect is an important influencing factor [ 17 19 ], and that a lesion range of 15 mm, lack of fracture displacement, and locaton of injury in the anterolateral talus [ 20 , 21 ] often suggest a better prognosis. In contrast, the prognosis is poor when the range is larger than 15 mm, the lesion is located on the medial side, and there is subchondral cystic degeneration and intra-articular osteophyte formation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies and general underreporting of data make it difficult to pool data, which furthermore makes it difficult to draw conclusions about effectiveness of the use of scaffold in the treatment for OLT. As Hannon et al[ 15 ] described, adequate reporting of data in the studies of the treatment for OLT should be required to perform high quality studies, and investigators should be encouraged to implement data collection both before and after surgery according to recommended list described by Hannon et al[ 15 ] in this review, the categories of imaging data were reported in 73% of included studies. Compared with reporting of outcome data on microfracture for OLT in the systematic review by Hannon et al[ 15 ], imaging data was reported in only 39% among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two reviewers independently extracted data from each study and assessed variable reporting of outcome data using parameters of previously published criteria[ 15 ]. In addition, clinical outcomes and the percentage of patients who returned to sport at previous level were evaluated.…”
Section: Methodsmentioning
confidence: 99%